Long-term survival of a 6-year-old with trisomy 18 after cardiac intervention: The emerging need for comprehensive guidelines beyond the newborn period. (June 2020) - Key, Phillip; Qiryaqoz, Zeena; Sikkema, Megan; Letherer, Arianna; Harden, Jamie
Abstract: Trisomy 18 is a well-documented cause of spontaneous abortions. When live births do occur, median survival time has been estimated between two and fourteen days. This severely shortened life expectancy is attributed to potentially lethal congenital malformations involving the heart, central nervous system, and gastrointestinal system, among others. Infrequently, affected children survive beyond a year and evidence suggests this may become more common due to increased willingness to intervene in the neonatal period and the success of surgical corrections. This case report documents how a six-year-old female with trisomy 18 has challenged provider expectations and gives perspective in an emerging treatment gray-zone. Highlights: Trisomy 18 has traditionally been considered incompatible with life. Neonatal intensivists and cardiologists are more willing to surgically intervene. Benefits seen from intervention in newborn period create uncertainty in prognosis. Case of 6-year-old female with trisomy 18 who is clinically stable after intervention.